Boosting the inherent activity of NiFe layered double hydroxide via erbium incorporation for water oxidation - Yang, Jitao; Yang, Yibin (Frontiers in Chemistry, 2023)
Enhancing the inherent activity of transition metal-based compounds involving Ni and Fe for the electrocatalytic oxygen evolution reaction (OER) is of vital importance, especially NiFe layered double hydroxide (LDH). Here, we doped erbium (Er) into NiFe LDH (Er–NiFe LDH) nanostructures using simple liquid-phase synthesis. The OER activity tests at the same mass loading demonstrated that Er–NiFe LDH has a smaller overpotential and lower Tafel slope than undoped NiFe LDH and commercial RuO2 powders, needing only a small overpotential of 243 mV to achieve a constant current at 10 mA cm-2. Additionally, Er–NiFe LDH was grown in situ on hydrophilic carbon paper substrates (Er–NiFe LDH@CP) to fabricate a three-dimensional (3D) electrode with large catalyst loading, which is favorable for analyzing the stability of morphology structure and elementary components after OER measurement. The galvanostatic measurement suggested that the Er–NiFe LDH@CP electrode possess higher electrochemical durability than a modified glassy carbon electrode due to the stronger mechanical binding between Er–NiFe LDH nanostructures and carbon paper substrate. More importantly, physical characterizations (e.g., SEM and XPS) revealed that Er–NiFe LDH has an excellent stability of morphology, and Ni, Fe, and Er still exist on the catalyst 24 h after the operation. This work provides an effective way for improving the inherent catalytic activity and stability of polymetallic OER catalysts in the future.